Tampilan gigi insisivus maxillaris dan koridor buccal pada senyum - Annisaa Putri Ariyani; Syifa Sistasia; Wita Anggraini; Indrani Sulistyowati (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Smile is one of the important things that would be noticed when communicating with someone; therefore, the aesthetics and appearance of a smile are important for both men and women. Smile analysis will assist the dentist in making a diagnosis and planning treatment depending on the balance and alignment of the smile components. The maxillary incisor display and the buccal corridor are two components that need attention to get an aesthetic and attractive smile.